Analisis Wacana Kritis Slogan Politik “MENUJU SELUMA ALAP” Pada Pemilihan Kepala Daerah Kabupaten Seluma 2020 - Fahruri (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2022)
This research was conducted with the background of critical discourse analysis of one of the slogans of the regional head election in the Seluma regional head election. This study aims to: (1) find out the political meaning of the slogan "Menuju Seluma Alap" in the 2020 Seluma election, (2) find out why the political slogan "Towards Seluma Alap" was used in the 2020 Seluma election. This research is a qualitative research. Discourse descriptions and political slogan messages on political slogans contain messages, meanings, invitations and background in the tribal language in Seluma district. Keywords: Critical discourse analysis and political slogans